Adopted Material Properties of Historical Masonry Structures for Finite Element Models: Mosques and Bridges - Onat, Onur; Yön, Burak (Fırat University, 2018)
This paper aims to present adopted material properties of masonry elements to historical mosque and bridge structures. The importance of this study is to adopt correct material properties with reliable reference according to material types and structure types.
Keywords: Engineering; Mühendislik